Effect of the landscape context on the density and persistence of a predator population in a protected area subject to environmental variability - Baeza, Andrés; Estades, Cristián F. (Biological conservation, 2010)
Protected areas are the most important tool for the conservation of biodiversity. However, many species are area-demanding and their populations seldom meet their space requirements in reserves. In this context, the unprotected exterior becomes an important part of their home range, and variations in habitat quality of the surroundings of a protected area might affect the dynamics of populations. Using a spatially explicit simulation model, we studied the effect of the surrounding landscape of a protected area on the density and persistence of a predator population inhabiting inside the reserve in different conditions of environmental variability. We simulated individuals of a predator population, their herbivorous prey and a vegetative substrate in a landscape comprised of a square protected area and different types of habitat quality outside the reserve. We studied the combination of three substrate qualities of protected area (inside) with three of the landscape context and three levels of variability of productivity. Our results showed that there were strong effects of both the relative quality of the surrounding landscape and of the environmental variability on the density and persistence of the simulated population inside the protected area. More importantly, we showed that complex patterns emerge when spatial heterogeneity and temporal variability interact with population dynamics. Specifically, under high environmental variability, when the protected area had a high habitat quality, the highest population persistence was not attained when the exterior was also of high quality, but when the surroundings had an intermediate quality. The latter result suggests that, under the mentioned conditions, small enhancements in the quality of the matrix may have, for some species, better effects on increasing persistence in small reserves than large and costly enhancements.